Os gêneros poéticos em livros didáticos de língua portuguesa do ensino fundamental: uma abordagem enunciativo-discursiva - Padilha, Simone de Jesus (2005)
The present work discusses the question of the literary reader s formation in classes of the Brazilian public school system s elementary level by means of an analysis of the way texts in poetical genres are approached on didactical manuals customarily used on Portuguese Language classes. Its basis is the theorizations done by the Bakhtin s Circle about poetic discourse, mainly its critiques of material aesthetics and Russian Formalism. Bakhtin s notion of discourse genre has been its guiding principle, chiefly as regards questions related to compositional form, style and theme, seeing poetic texts as aesthetic objects. We examined the theoretical genres poems, lyrics and some other oral tradition ones as regards their insertion in the school system by manuals, arguing on the basis of the Bakhtinian concepts of chronotope and genre memory for their consideration as a possible grouping aiming to rethinking their didactisation. The research methodology aimed to select the collections more apt to present a space for investigating the work done with the poetical genres here studied, using data banks from the Integrated Research Project, O livro didático de Língua Portuguesa no ensino fundamental: produção, Perfil e Circulação, CNPq/IEL-UNICAMP/CEALE-UFMG, a research that examines data resulting from evaluations done in the context of the Brazilian National Program of Manuals and creates several data banks. We have done a quantitative and qualitative analysis of 4 collections of Portuguese Language for the 1st to 4th grades and 3 for the 5th to the 8th grades. The quantitative analysis explored data relative to the poetical genres incidence, position and authorship and the qualitative one examined the activities the manuals proposed to texts in poetical genres, identifying different ways to approach the literary. Data analysis shows the collections do not favor the literary reader s formation in the fundamental level, for they do not take genres as teaching objects, do not use them for reading activities and give prominence only to the texts formal aspects or the pupil-reader subjectivity. As a rule, the examined books do not offer activities that favor the construction of poetical texts reading and more than this their do not take into account their enunciative-discursive dimension